The origins of semitic languages - Yaacob, Solehah@Nik Najah Fadilah; Yeob, Shamsul Jamili (IIUM Press, 2011)
`Semitic` is a word introduced by Schlozer in 1780 to denote the group of languages evolved from Aramaic, Pheonic, Hebrew, Arabic, Yemen, Babylonian and Assyrian. He understood them to be languages of the descendents of Prophet Noah. From the time of the Upper Palaeolithic age, the descendents of Adam were the founders of human civilization. Their success depended on the stability of their political, cultural and geographical structures, and linguistic study is a vital aid in the analysis of their development. The major written cultures of the ancient Near East have produced the largest body of material providing with a sound basis for subsequent reflections on their linguistic diversity and attempts at contrastive linguistics with Mesopotamia. E. Reiner asserted that at the beginning of recorded human history there existed two major languages side by side, Acadian and Sumerian. He assumed that the Acadian of the Semitic people spread to Mesopotamia by way of migration around 4ooo B.C.E. If we look at the Upper Paleolithic, Mesolithic, Neolithic and Chalcolithic times.